2014
DOI: 10.2147/ijn.s49616
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development and optimization of palm kernel oil esters-based nanoemulsions containing sodium diclofenac

Abstract: Response surface methodology was employed to study the effect of formulation composition variables, water content (60%–80%, w/w) and oil and surfactant (O/S) ratio (0.17–1.33), as well as high-shear emulsification conditions, mixing rate (300–3,000 rpm) and mixing time (5–30 minutes) on the properties of sodium diclofenac-loaded palm kernel oil esters-nanoemulsions. The two response variables were droplet size and viscosity. Optimization of the conditions according to the four variables was performed for prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
13
0
2
Order By: Relevance
“…For emulsification by lowenergy methods, composition variables have much higher influence than preparation variables. 64 Our results agreed with other studies, 58,60 which showed that increased water fraction resulted in an increase in particle sizes.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…For emulsification by lowenergy methods, composition variables have much higher influence than preparation variables. 64 Our results agreed with other studies, 58,60 which showed that increased water fraction resulted in an increase in particle sizes.…”
supporting
confidence: 92%
“…Our results are consistent with research showing that particle size increases with increasing water content. 60 Increasing water content eliminates rigid film, leading to coalescence of droplets and increased particle size. …”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…Combined interactions of medium physical parameters for the production of the desired product are large and the optimum process conditions may be developed using an effective experimental design procedure 12, 15. RSM, which is a collection of statistical techniques for design of experiments, building models, measured responses, evaluating the effects and relationship between clusters of controlled experimental factors and searching for the optimum conditions, has successfully been used in the optimization of bioprocesses 15, 16. A prior knowledge with understanding of the related bioprocesses is necessary for achieving a more realistic model.…”
Section: Methodsmentioning
confidence: 99%
“…14 Nanoemulsions can be prepared by high-energy emulsification or by low-energy emulsification methods. 15 However, nanoemulsions are thermodynamically unstable colloidal systems that are highly dependent on their physicochemical properties, usually based on the preparation method. 14 Thus, a precise preparation method is necessary to avoid overprocessing, which will be a waste of time and cost.…”
mentioning
confidence: 99%